What affects implementation of green buildings? An empirical study in Hong Kong - Vivian W. Y. Tam; Jane L. Hao; S. X. Zeng (International Journal of Strategic Property Management, 2012)
This paper examines the factors affecting the implementation of green buildings for the local construction industry. Questionnaire surveys and structural interviews were conducted to investigate the economical and social factors in the implementation of green buildings. From the survey results, the industry strongly believes that green building implementation is environment-friendly and can improve social values to the consumers. However, material costs, construction and transportation for green materials and green building features are more expensive than those for the conventional buildings. Four major factors affecting the existing limited implementation of green buildings were also discussed. Recommendations to improve the implementation of green buildings were also explored. This study can bring insights locally and around the world on how green buildings can be implemented to achieve environment-friendly, long-term cost saving and being recognized by the society and the consumers to reduce difficulties and burden encountered in the implementation.